A report of the complete mitochondrial genome of Bisetocreagris titanium (Arachnida: Pseudoscorpiones: Neobisiidae) from Yunnan Province, China. Issue 11 (2nd November 2021) - Zhao, Huifeng; Chen, Haifeng; Li, Yunchun
Abstract: A complete mitogenome of a cave dwelling pseudoscorpion Bisetocreagris titanium is reported here. The mitogenome is a circular DNA molecule with a length of 14, 756 base pairs (bp), and it contains 13 protein coding genes (PCGs), 22 transfer RNAs (tRNAs), 2 ribosomal RNAs (rRNAs), and 1 putative control region. Phylogenetic analysis of 30 Arachnida species was performed based on the amino acid datasets of 13 PCGs, and the result indicated Pseudoscorpiones is the sister lineage of Acariformes. This result is congruent with the former phylogenetic results of mitogenomes, but incongruent with the results of morphological characters and/or ribosomal DNA data that indicated Pseudoscorpiones are positioned in a clade with the Solifugae.